Mental Health Clinician and Community Clergy Collaboration to Address Moral Injury in Veterans and the Role of the Veterans Affairs Chaplain. Issue 1 (2nd January 2019) - Pyne, Jeffrey M.; Rabalais, Aline; Sullivan, Steve
Abstract : Moral injury in veterans with posttraumatic stress disorder includes symptoms of guilt and shame, and these symptoms are often not responsive to evidence-based mental health treatments. Clergy provide a pathway for relieving the guilt and shame. However, there is a long history of mistrust between clergy and mental health clinicians and not enough Veterans Health Administration chaplains to meet this need. The goal of this study was to gather qualitative interview data from relevant stakeholders regarding whether and how Veterans Affairs (VA) mental health clinicians and community clergy could collaborate to address moral injury issues such as guilt and shame in veterans being treated for posttraumatic stress disorder. The stakeholders for this study were veterans, mental health clinicians, and clergy. Qualitative data were organized into three domains: barriers, facilitators, and intervention suggestions. These data were used to develop a new intervention for moral injury that includes a central role for the Veterans Affairs chaplain.